PENGARUH MODEL OUTDOOR LEARNING TERHADAP KREATIVITAS MELUKIS SISWA PADA PEMBELAJARAN SENI RUPA DI SEKOLAH DASAR - Nasywaa Nurjihaan Aziizah; Luthfi Hamdani Maula; Irna Khaleda Nurmeta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the influence of the Outdoor Learning Model onstudents' painting creativity at SDN Cisarua in the odd semester of the 2024/2025academic year. The subjects of this research were 30 class V students who wereselected using purposive sampling. The Outdoor Learning model was chosenbecause it was considered capable of providing a more enjoyable and effectivelearning experience in increasing student creativity, especially in fine arts learning.The research method used is a Quasi Experimental method with a pretest-posttestcontrol group design research design. Data collection techniques were carried outusing instruments in the form of test sheets and performance assessments toassess the results of students' painting creativity. Data analysis was carried out withthe help of IBM SPSS Statistics version 30 software, using several statisticaltechniques such as validity tests, reliability tests, homogeneity tests, and t tests. Theresearch results showed that there were significant differences between theexperimental group that used the Outdoor Learning Model and the control groupthat used conventional methods. The average painting creativity score for theexperimental group (87.27) was higher than the control group (79.13). With asignificance value of 0.0001<0.05, it can be concluded that the Outdoor LearningModel has a positive impact on students' painting creativity. Therefore, this modelis suitable for application in fine arts learning in elementary schools.